Fear of the Monsters in H.P. Lovecraft’s Short Stories “Whisperer in the Darkness” (1930) & “At the Mountain of Madness” (1931): Freudian Psychology of the Uncanny - Titis Tri Ningtyas; Ali Mustofa (English Department - University of Sultan Ageng Tirtayasa, 2022)
An encounter with ominous objects or situations that causes one to feel uneasy, frightening, or afraid is known as an uncanny experience. It involves both feelings and situations that make someone uneasy. This article focused on the uncanny feelings in Lovecraft's two well-known short stories,